TBK1 and IKKε prevent TNF-induced cell death by RIPK1 phosphorylation - Lafont, Elodie; Draber, Peter; Rieser, Eva; Reichert, Matthias; Kupka, Sebastian; de Miguel, Diego; Draberova, Helena; von Mässenhausen, Anne; Bhamra, Amandeep; Henderson, Stephen; Wojdyla, Katarzyna; Chalk, Avigayil; et al. (Nature cell biology, 2018)
The linear-ubiquitin chain assembly complex (LUBAC) modulates signalling via various immune receptors. In tumour necrosis factor (TNF) signalling, linear (also known as M1) ubiquitin enables full gene activation and prevents cell death. However, the mechanisms underlying cell death prevention remain ill-defined. Here, we show that LUBAC activity enables TBK1 and IKKε recruitment to and activation at the TNF receptor 1 signalling complex (TNFR1-SC). While exerting only limited effects on TNF-induced gene activation, TBK1 and IKKε are essential to prevent TNF-induced cell death. Mechanistically, TBK1 and IKKε phosphorylate the kinase RIPK1 in the TNFR1-SC, thereby preventing RIPK1-dependent cell death. This activity is essential in vivo, as it prevents TNF-induced lethal shock. Strikingly, NEMO (also known as IKKγ), which mostly, but not exclusively, binds the TNFR1-SC via M1 ubiquitin, mediates the recruitment of the adaptors TANK and NAP1 (also known as AZI2). TANK is constitutively associated with both TBK1 and IKKε, while NAP1 is associated with TBK1. We discovered a previously unrecognized cell death checkpoint that is mediated by TBK1 and IKKε, and uncovered an essential survival function for NEMO, whereby it enables the recruitment and activation of these non-canonical IKKs to prevent TNF-induced cell death.
Keywords: Animals; HeLa Cells; ubikvitinace; Tumor Necrosis Factor-alpha; Mice, Knockout; myši knockoutované; lidé; HeLa buňky; kinasa I-kappa B; A549 Cells; signální transdukce; Protein Serine-Threonine Kinases; serin-threoninkinasy interagující s receptory; kultivované buňky; Signal Transduction; buněčná smrt; Cells, Cultured; TNF-alfa; Receptors, Tumor Necrosis Factor, Type I; fosforylace; I-kappa B Kinase; Cell Death; Ubiquitination; receptory TNF - typ I; zvířata; protein-serin-threoninkinasy; buňky A549; Phosphorylation; Receptor-Interacting Protein Serine-Threonine Kinases; Humans